Evaluation de la qualité de vie des femmes souffrant d’une fistule obstétricale à Kinshasa [Evaluation of the quality of life of women with obstetric fistula in Kinshasa] - Jonathan Enguta Mwenzi; Ruth Bukabau Babuya; Francine Manyonga Sabowa (Journal de la Faculté de Médecine d'Oran)
Fench Abstract :